Angiopoietin‐like protein 1 antagonizes MET receptor activity to repress sorafenib resistance and cancer stemness in hepatocellular carcinoma - Chen, Hsin‐An; Kuo, Tsang‐Chih; Tseng, Chi‐Feng; Ma, Jui‐Ti; Yang, Shu‐Ting; Yen, Chia‐Jui; Yang, Ching‐Yao; Sung, Shian‐Ying; Su, Jen‐Liang (Hepatology (Baltimore, Md.), 2016)
Angiopoietin‐like protein 1 (ANGPTL1) has been shown to act as a tumor suppressor by inhibiting angiogenesis, cancer invasion, and metastasis. However, little is known about the effects of ANGPTL1 on sorafenib resistance and cancer stem cell properties in hepatocellular carcinoma (HCC) and the mechanism underlying these effects. Here, we show that ANGPTL1 expression positively correlates with sorafenib sensitivity in HCC cells and human HCC tissues. ANGPTL1 significantly decreases epithelial‐mesenchymal transition (EMT)‐driven sorafenib resistance, cancer stemness, and tumor growth of HCC cells by repressing Slug expression. ANGPTL1 directly interacts with and inactivates MET receptor, which contributes to Slug suppression through inhibition of the extracellular receptor kinase/protein kinase B (ERK/AKT)‐dependent early growth response protein 1 (Egr‐1) pathway. ANGPTL1 expression inversely correlates with Slug expression, poor sorafenib responsiveness, and poor clinical outcomes in HCC patients. Conclusion: ANGPTL1 inhibits sorafenib resistance and cancer stemness in HCC cells by repressing EMT through inhibition of the MET receptor−AKT/ERK−Egr‐1−Slug signaling cascade. ANGPTL1 may serve as a novel MET receptor inhibitor for advanced HCC therapy. (Hepatology 2016;64:1637‐1651)